Pelaksanaan Fungsi Badan Permusyawaratan Desa Di Desa Bayondo Kecamatan Tomoni Kabupaten Luwu Timur - Sukmawati, Dewi; Usman, Jaelan; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
Abstract This study aimed to describe and eplainevthe implementation of the function Village Consultatie Body (BPD) in Bayondo Village, Tomoni District, East Luwu Regency. This study used a qualitaive descriptive method. Data collection techniques through observation and interviews. The results of this study showed that the implementation of the function (BPD) was know that the function discussed and agreeing that the draft Village regulation had been implemented and realized optimally, the function of accommodating and channeling the aspirations of the community had not been implemented well, his was because there were still obstacles in its implementation, where the comunity still did not understand the duties and functions performed by the BPD, so that in the implementation process it accommodates and channels community asprations often get opposition and debate from society, function supervising the performance of the village head was not maximal due to lack of communication between BPD administrators. Keywords: bpd function, implementation, village government